Publication and scientific visibility in communication. The Latin America case (Herald of Journalism, 2023)
Scientific production on communication issues in the world is increasing and can be evidenced in the visibility records of authors and studies in journals of high scientific impact. However, in regions such as Latin America, this production is not as desired, and continues to suffer from satisfactory indicators of visibility of the efforts of institutions and researchers. This is revealed by the exploratory research and technological surveillance and strategic intelligence carried out from the Scopus database, in observance of the Scimago Journal and Country Rank (SJR) classification in the period 2018-2022, and in comparison with the scientific production of the periods 2014-2019 and from 2000 to 2022.The visibility of scientific production in high-impact journals (quartiles: 1, 2, 3 and 4) reveals that Latin America increased not only research, but also scientific production in communication during the period 2018-2022. An unfinished formation and conformation of the field of communication deserves to listen to the heartbeat of all regions of the world (Torrico, 2011) and provoke reflection on the constitutive history of the field of knowledge, as well as communication research (Vidales, 2015), at times in which science has and can access greater possibilities for its strengthening.
Keywords: technological surveillance, communication research, scientific production, scientific visibiliy, Latin America.